The Role of Parasites in Acute Appendicitis of Pediatric Patients - Dorfman, Saul; Cardozo, José; Dorfman, Denny; Del Villar, Alonso (Investigación Clínica, 2009)
There is little evidence regarding the relationship between parasites and acute appendicitis. In order to determine such a relationship, if any, 830 appendectomy specimens were studied. Age, sex, pathological findings and the presence and type of parasites and the type of parasite were analyzed. Parasites were present in 62 cases (7.46%). Ascaris lumbricoides and Trichuris trichiura were the most frequently encountered parasites. These were observed, alone or in combination, in 45 cases (72.5%). Appendix perforation, peritonitis, necrosis and flegmonous appearance, were more frequent in the cases of acute appendicitis without parasitic infestation (p < 0.05). There were no differences between the cases with or without parasitic infestation (p > 0.05) In cases of peritonitis. The low incidence of parasites among the appendectomy specimens and the failure to demonstrate its relationship with all events derived of appendicitis, do not support the hypothesis that parasites are a major cause of appendicitis in pediatric patients